Microencapsulation of probiotic bacteria - Rocha, João Miguel Ferreira (2016)
This manuscript describes some general reflections on the research around the microencapsulation and its application in the preparation of stable consortia of probiotic bacteria. Its predominant application focuses on the agro-food, nutraceutical and pharmaceutical industry but despite the highest industrial interest, the wide diversity of applications and the existence of a broad and diversified consumer market yet to be explored, there is still a quite long way to go to improve the bioactivity, functionality and applicability of these innovative (bio) technological products.